(untitled) (Brazilian Journal of Oceanography, 2009)
The distribution and abundance of the lesser electric ray, Narcine brasiliensis, was assessed based on bottom-trawl survey data collected off the coast of Rio Grande do Sul, southern Brazil. Between 1980 and 1984 and in 2005, 416 bottom trawl hauls were carried out at depths of 10-100 m. Narcine brasiliensis occurred mainly in waters with bottom temperature between 20 and 25ºC. Density of the species was higher between the depths of 10 and 20 m, during the summer and autumn. The seasonal pattern of N. brasiliensis in the shallow coastal water of Rio Grande do Sul reflects a southward migration in summer. This is conditioned by the southward advance of warmer and high-salinity Tropical Water of the Brazil Current In winter, the return or northward migration is a response to seasonal cooling of the coastal waters and to the northward advance of cold Coastal Water of lower salinity. The latitudinal gradient in density of N. brasiliensis was related to the latitudinal gradient in salinity of the bottom waters. This was caused by the freshwater runoff from the Patos Lagoon establishing a physical barrier to the occurrence of the species farther south than the city of Rio Grande.